2022
DOI: 10.1016/j.asmr.2021.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation, Restrictions, and Return to Sport After Cartilage Procedures

Abstract: The ability to return to sport (RTS) after articular cartilage injury is of vital importance to athletes. Discussing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…other factors. 13,20,31 Moreover, the small number of professional athletes with these injuries are subject to coaching decisions, match-ups, and availability of other players, all of which affect their timing for return. 20 Clinical outcomes significantly improved in each PRO measured postoperatively at final follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…other factors. 13,20,31 Moreover, the small number of professional athletes with these injuries are subject to coaching decisions, match-ups, and availability of other players, all of which affect their timing for return. 20 Clinical outcomes significantly improved in each PRO measured postoperatively at final follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, however, return-tosport literature must be interpreted with some degree of caution given the many independent variables, beyond the treatment of the articular cartilage defect itself, that are influential determinants related to returning an athlete to his or her preinjury status. 20,31 The purpose of this study was to evaluate the experience of the senior author (B.J.C.) in treating professional athletes by means of osteochondral allograft transplant, including analyzing clinical outcomes and return to sport.…”
mentioning
confidence: 99%
“…Previous studies have reported return-to-play rates ranging from 54% to 88% after OCA transplantation in non-professional athletes. 16 , 17 , 18 , 19 , 20 In a recent case series of professional basketball players, Balazs et al. 21 reported an overall rate of return to play at the same level of 80% after a mean of 14 months’ follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…[164] In the longer term, the time to return to active sport can range between 6 and 18 months, with differences based on treatment strategies. [168,169] Data for post-operative care following novel tissue engineering implantation is more sparse, and so optimum strategies are yet to be defined. [166] Though it is well understood that mechanical stimulation is critical for healthy cartilage metabolism, how much joint motion and weight bearing is beneficial (but not detrimental) to the maturation of an in situ engineered bioscaffold is unclear.…”
Section: Post-operative Carementioning
confidence: 99%
“…[ 164 ] In the longer term, the time to return to active sport can range between 6 and 18 months, with differences based on treatment strategies. [ 168,169 ]…”
Section: A Comparison or Ex Situ And In Situ Tissue Engineering Strat...mentioning
confidence: 99%